Endogenous PP2A inhibitor CIP2A degradation by chaperone-mediated autophagy contributes to the antitumor effect of mitochondrial complex I inhibition - Cazzoli, Riccardo; Romeo, Francesco; Pallavicini, Isabella; Peri, Sebastiano; Romanenghi, Mauro; Pérez-Valencia, Juan Alberto; Hagag, Eman; Ferrucci, Filippo; Elgendy, Mohamed; Vittorio, Orazio; Pece, Salvatore; Foiani, Marco; et al. (Cell reports, 2023)
Combined inhibition of oxidative phosphorylation (OXPHOS) and glycolysis has been shown to activate a PP2A-dependent signaling pathway, leading to tumor cell death. Here, we analyze highly selective mitochondrial complex I or III inhibitors in vitro and in vivo to elucidate the molecular mechanisms leading to cell death following OXPHOS inhibition. We show that IACS-010759 treatment (complex I inhibitor) induces a reactive oxygen species (ROS)-dependent dissociation of CIP2A from PP2A, leading to its destabilization and degradation through chaperone-mediated autophagy. Mitochondrial complex III inhibition has analogous effects. We establish that activation of the PP2A holoenzyme containing B56δ regulatory subunit selectively mediates tumor cell death, while the arrest in proliferation that is observed upon IACS-010759 treatment does not depend on the PP2A-B56δ complex. These studies provide a molecular characterization of the events subsequent to the alteration of critical bioenergetic pathways and help to refine clinical studies aimed to exploit metabolic vulnerabilities of tumor cells.
Keywords: cancer; respirační komplex I; Protein Phosphatase 2; nádorové buněčné linie; signální transdukce; Chaperone-Mediated Autophagy; OXPHOS; CIP2A; Autoantigens; Signal Transduction; Energy Metabolism; oxidativní fosforylace; Cell Line, Tumor; CP: Cancer; autofagie zprostředkovaná chaperony; fasting; Oxidative Phosphorylation; chaperone-mediated autophagy; Neoplasms; energetický metabolismus; proteinfosfatasa 2; Humans; nádory; autoantigeny; Electron Transport Complex I; CP: Molecular biology; metabolism; PP2A; lidé; glycolysis